Xanthogranulomatous Cholecystitis and Gallbladder Cancer: Two Diseases with Difficult Differential Diagnoses - Akkurt, Gökhan; Birben, Birkan; Çoban, Serdar; Akgül, Özgür; Kulaçoğlu, Sezer; Doğanay, Mutlu (Turkish Journal of Gastroenterology, 2021)
Background: Xanthogranulomatous cholecystitis (XGC) etiology has not yet been precisely determined; it is often confused with gallbladdercancer (GBC) in the differential diagnosis.Methods:: This study retrospectively evaluated patients who underwent surgery with the pre-diagnosis of cholelithiasis, cholecystitis,or gallbladder carcinoma at a tertiary center, and were confirmed to have XGC or GBC according to the histologicalexaminations.Results: In the GBC group, there was a higher number of female patients, patients with magnetic resonance imaging (MRI) and computedtomography (CT) imaging, those that directly underwent open surgery, and those requiring catheters and developed complications;while in the XGC group, there was a higher number of patients with ultrasonography (USG) imaging and those requiring conversionfrom laparoscopic to open surgery (P < .05). The rate of patients with a preoperative diagnosis of cholelithiasis was higher in the XGCgroup than in the GBC group, and cases with intrahepatic bile duct (IHBD) dilatation were higher in the GBC group than in the XGCgroup, and the GBC group also had a higher rate of cases with a malignant diagnosis in the preoperative examination compared to theXGC group (P < .05).Conclusion: When a suspicious malignant mass is detected in the localization of the gallbladder, XGC must be considered in the differentialdiagnosis. Although it is not a malignant pathology, early diagnosis and treatment are particularly important due to the associatedcomplications and the possibility of coexistence with GBC.